Can green finance improve carbon emission efficiency? Evidence from China - Liang, Jinhao; Song, Xiaowei (Frontiers in Environmental Science, 2022)
Green finance provides ample financial guarantee for economic green and low-carbon transformation, and provides opportunities for improving China's carbon emission efficiency. Based on the macro-panel data of 30 provinces in China from 2010 to 2019, this paper uses fixed effect model and spatial Durbin model to study the impact of green finance on regional carbon emission efficiency. The results show that: First, the development of green finance can improve the carbon emission efficiency; Second, in addition to the "local effect", the influence of green finance on carbon emission efficiency has a "neighborhood effect", that is, it has a spatial spillover effect on carbon emission efficiency in neighboring areas, and this effect only exists in a short time; Third, the impact of green finance on carbon emission efficiency is heterogeneous in different regions with different environmental regulations.